A model of corporate culture, strategic change and corporate performance: an empirical study of the Chinese construction industry. (9th March 2021) - Liu, Mingming; Freeman, Susan; Murad, Md. Wahid
Drawing upon strategy and organisational theories and practices, we develop a model of corporate culture, strategic change and corporate performance extending the current conceptualisations of 'corporate culture' and 'strategic change'. Using data obtained from 244 Chinese construction firms our empirical results show that internal organisational factors significantly influence corporate change and hence corporate performance. In this study, strategic change is found to not only influence structures and processes, but it also lends support to the cognitive organisational reorientation approach to understand relationships. We contribute new understanding, showing that team spirit and social responsibility have a positive influence, while science and technological innovation and organisational learning have a negative influence on strategic change speed, magnitude and depth. Customer orientation did not meet the requirements of factor analysis and strategic change was found to have no intervening influence on the relationship between corporate culture and corporate performance.